Addressing the problem of sub-optimal productivity and curcumin content of turmeric in low input rainfed agricultural system - Mishra, A; Mishra, A; B Behera, B S Rath, S K Mohanty, (Journal of Spices and Aromatic Crops, 2017)
Field experiments were conducted at AICRP for Dryland Agriculture, Orissa University of Agriculture & Technology, Phulbani, Odisha (India) to study the yield performance of 10 important turmeric genotypes, and the effect of five different nutrient management practices on four outstanding varieties in order to address the problem of low rhizome yield and curcumin content of the zone. Based on yield data of 10 turmeric varieties over two years (2007 and 2008) evaluated in RBD with three replications, highest rhizome yield of 21.7 t/ha was observed in Lakdong followed by Rajendra Sonia (16.0 t/ha). The second experiment was laid out in factorial design involving four varieties and five nutrient treatments with 3 replications. The yield data over five years (2009-10 to 2012-13 and 2014-15) shows Lakdong (9.14 t/ha) to be the best among varieties and lime @10% LR + 50% organic + 50% inorganic (9.15 t/ha) among nutrient treatments. Significant variety × nutrient interaction was observed with respect to rhizome yield. Highest rhizome yield was obtained from turmeric variety Lakdong with 100% organic treatment (11.1 t/ha). While two varieties, Lakdong and Phulbani Local exhibited highest yield with 100% organic treatment, performance of Rajendra Sonia was the best with 50% organic + 50% inorganic + lime @10% LR and Roma with 50% organic + 50% inorganic. Significant variation was observed among nutrient treatments of all four turmeric varieties for NPK content in shoot and rhizome. The interaction between varieties and nutrient management practices for curcumin content was significant.